Cannabis in Danish newspapers - Houborg, Esben; Enghoff, Oscar (Tidsskrift for Forskning i Sygdom og Samfund, 2018)
Using quantitative methods Danish cannabis debate in national newspapers is investigated. The investigation shows that the most prevalent topics relate to law enforcement. Legalization has become an increasingly important topic in the Danish cannabis debate and the investigation shows a reframing of this debate to become increasingly related to concerns about organized crime. In this way the Danish cannabis legalization debate show the same development as the debates that have led to legalization certain states in the United States of America.